Fighting by sleep-deprived rats as a possible manifestation of panic: effects of sodium lactate - Furlan, F.A. (2001)
Increased fighting is an effect of desynchronized sleep deprivation (DSD) in rats, and recently this behavior has been suggested to be spontaneous panic and equivalent to panic disorder. In the present study we tested this hypothesis by evaluating the effect of sodium lactate on this aggressiveness, because this substance is recognized to induce spontaneous panic attacks in patients. A total of 186 male albino Wistar rats, 250-350 g, 90-120 days of age, were submitted to DSD (multiple platform method) for 0, 4, or 5 days. At the end of the deprivation period the rats were divided into subgroups respectively injected intraperitoneally with 1.86, 2.98 and 3.72 g/kg of 1 M sodium lactate, or 1.86 and 3.72 g/kg of 2 M sodium lactate. The control animals were submitted to the same procedures but received equivalent injections of sodium chloride. Regardless of DSD time, sleep-deprived animals that received sodium lactate presented a significantly higher mean number of fights (0.13 ± 0.02 fights/min) and a longer mean time spent in confrontation (2.43 ± 0.66 s/min) than the controls (0.01 ± 0.006 fights/min and 0.12 ± 0.07 s/min, respectively; P<0.01, Student t-test). For the sodium lactate group, concentration of the solution and time of deprivation increased the number of fights, with the mean number of fights and mean duration of fighting episodes being greater with the 2.98 g/kg dose using 1 M lactate concentration. These results support the hypothesis that fighting induced by DSD is probably a spontaneous panic manifestation. However, additional investigations are necessary in order to accept this as a promising animal model for studies on panic disorder.